Strategi Pemasaran Jeruk Keprok Batu 55 Pada Kelompok Tani Subur Makmur Desa Selorejo Kecamatan Dau, Kabupaten Malang di Masa Pandemi COVID-19 - IRWANTO, FAUZY DILI; AMBARAWATI, I G. A. A.; DARMAWAN, DWI PUTRA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.12, No.2, Desember 2023, 2023)
Marketing Strategy for Tangerine Batu 55 on the Subur Makmur Farmers Group Selorejo Village, Dau District, Malang Regency in the COVID-19 Pandemic.  East Java province as the largest producer of oranges in Indonesia from 2017 to 2021 has one district that consistently has production growth. This research raises the issue of the right marketing strategy for Subur Makmur farmer groups to be able to compete in the marketing of Tangerine Batu 55. Data collection methods used are interviews, documentation and literature studies. The data analysis used is SWOT Analysis. The results showed that the analysis of the internal environment has the power of being able to communicate with many consumers, dominate the market in East Java, the largest number of members, adequate quantity with good quality and known in Malang regency. The weakness is the use of internet media, often late delivery, the absence of cooperatives, farming capital, lack of coordination. Opportunities are the price of citrus fruits, having regular customers, the large number of market demand, the organization of well-known farmer groups and near tourist sites. The threat is the planting schedule, the abundance of competition. A marketing strategy that can be applied is to maintain to increase sales. Creating a product name to be known, opening a store around a tourist destination or a new place needs to be implemented. Market development using internal media also needs to be realized.